Performance evaluation on vanadium transport through supported liquid membrane by TOMAC as carrier - Nosrati, S.; Jayakumar, N.S.; Hashim, M.A.; Mukhopadhyay, S. (Elsevier, 2013)
Many industries use vanadium increasingly and as a consequence, the toxic effluents cause environmental concern. Here, we study the extraction of vanadium in supported ionic liquid membrane was studied. The effect of operational conditions on the process performance such as initial feed phase concentration, pH of the feed solution, pore size of the membrane support, type of ionic liquid charged on the support and stripping agent solution was investigated. Vanadium was effectively transported from the feed phase to the stripping phase of ammonia solution using the room temperature ionic liquid, tri-n-octyl methyl ammonium chloride (TOMAC) embedded in the support membrane. Selective transport of vanadium from its mixture with chromium ions was carried out applying TOMAC as the carrier. It was also observed that addition of a slight amount of a second room temperature ionic liquid, 1-butyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl] imide [BMIM][NTF2], improved the vanadium extraction process considerably.